Release coating for obtaining sand‑resin rods manufactured using heated tools - A. A. Pivovarchyk (Литьë и металлургия)
The article presents the results of research on the development of the lubricant composition for the production of sand‑resin rods over a heated tooling with high technological and consumer properties. It has been established that the conditional viscosity of the developed lubricant compositions decreases when oleic acid is added to the polymethylsiloxane liquid in an amount of 5 to 25 % from 10 to 8 s, and the density of lubricants is reduced from 908 to 882 kg/m3. It has been established that when oleic acid is added to the base in an amount of 15 %, the sedimentation stability of the lubricant is increased by more than 30 times. It is shown that the developed lubricant composition has the best lubrication characteristics at the following component ratio: base (polymethylsiloxane liquid PMS 300) 15 %, additive (oleic acid) 15 %, surfactant 3,0 %, water – the rest. The results of the research can be used by the process engineers when choosing the composition of the lubricant for making rods by the heated tooling.